PERAN CAMAT DALAM MENYELESAIKAN SENGKETA LAHAN DI KECAMATAN PANGKALAN KURAS KABUPATEN PELALAWAN TAHUN 2012 - Andri Syahrun Mubarhoq; M. Amin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The research present describe the rules of head district in .finished the conflict of land in Pangkalan Kuras District Pelalawan Regency in 2012. This conflict was begin when the Surya Bratasena Company was operated in Pangkalan Kuras. Cooperation form that negotiated by Surya Bratasena Company are plasma inti garden with the 3 village likes Terantang Manuk, Dundangan and Palas Village.The research use the methode are qualitative methodes that analyze problem research by describe the subject and object conditions based on real fact. This research use location in Pangkalan Kuras district Pelalawan Regency and researcher collect data from books, government regulation, jurnal, mass media, website and deep interview with Pangkalan Kuras Head of District, Terantang Manuk, Palas and Dundangan Head of village and Society in Pangkalan Kuras.The conclution of this research are the rules of head district in .finished the conflict of land in Pangkalan Kuras District Pelalawan Regency with coordination and mediation with the group that have a conflict likes Dundangan, Terantang Manuk and Palas Head of Village. In others Pangkalan Kuras Head of District also has done the mediation with create a discussion with Surya Bratasena Company and Pangkalan Kuras society.Keywords: rules, Head of district, conflict and land.